Periodontal diseases, potential mediators and development of liver fat content: a community-based large cohort - Liu, Bofu; Jia, Yu; Gu, Zhihan; Li, Yizhou; Zhou, Yiheng; Cao, Yu (Frontiers in Medicine, 2025)
BackgroundA high level of liver fat content (LFC) is a key indicator of steatotic liver disease (SLD), reflecting its pathological essence. Periodontal disease (PD) recognized as a chronic inflammatory condition and cause a widespread adverse health impact. This study aims to investigate the relationship between PD and LFC development.MethodsIn the UK Biobank, PD were gathered through a digital questionnaire, including gum pain, gum bleed, or teeth loose. LFC was measured by Fatty Liver Index (>60 indicates SLD) in cross-sectional analysis and by magnetic resonance imaging (quantified by Proton Density Fat Fraction, PDFF) in longitudinal analysis. Multivariable logistic and linear regression models were conducted to investigate the association of PD and LFC.ResultsIn cross-sectional analysis, 164,150 (37.4%) individuals were diagnosed with SLD, and PD showed a significant association with SLD (odds ratio: 1.104, 95% CI: 1.075–1.132). In prospective analysis, a total of 39,656 participants with a median follow-up of 10.3 years were included. PD showed an arithmetic mean difference of 0.091 in PDFF (95% CI: 0.047–0.139), with males exhibiting a stronger association than females (P for interaction <0.05). Significant mediating effects were observed for body mass index (19.58%), C-reactive protein (11.61%), blood glucose (6.70%), and healthy diet score (5.99%) between PD and PDFF (P for all <0.001).ConclusionThere was a pronounced correlation between PD and LFC, with males predominantly driving this link. This correlation may be partially mediated by body fat, inflammation, dietary habit, and insulin resistance.